Contemporary Dance in Music Education - Veler, Maša (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter examines the role of dance in education, its impact on understanding musical concepts, its integration into musical performances, and its contribution to developing interdisciplinary curricula. Dance education enhances engagement, fosters critical and creative thinking, and deepens comprehension of musical content, even though it is often marginalized due to limited resources and institutional support. Research (Fegley, 2010; Sears, 2012; Lau and Grieshaber, 2018) highlights dance as a powerful tool for storytelling and creativity, encouraging holistic learning and interdisciplinary connections. Integrating dance into musical performances enriches interpretation and emotional depth, while interdisciplinary approaches ensure equitable treatment of dance and other fields. Despite challenges, findings demonstrate that dance significantly enhances educational environments, underscoring the need for teacher support, further research, and the development of innovative teaching practices.